1970
DOI: 10.1084/jem.132.6.1233
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Heavy and Light Chain Antigenic Determinants on the Cell-Bound Receptor for Antigen

Abstract: High-rate antibody-forming cells and immunological memory cells can be selectively retained if filtered through a column coated with relevant antigen. This trapping can be blocked if the cells are incubated with an anti-immunoglobulin serum prior to column passage. A similar blocking is not observed when cells are treated with an anti-lymphocyte serum, thereby excluding the possibility that any antibodies combining with surface structures could cause this effect. By the use of antisera specific for heavy or li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

1971
1971
1976
1976

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(17 citation statements)
references
References 18 publications
1
15
0
1
Order By: Relevance
“…Since there are no IgG antibody-producing cells among ABC in low responder mice, it is clear that the ABC detected must be precursor or memory cells, which bear IgG on their surface. The formation of precursor cells of the IgG type after antigenic stimulation concurs with the findings of other investigators (30)(31)(32)(33). Furthermore, the results obtained show that in low responders the differentiation of IgG precursor or memory cells into IgG antibody-forming cells is not completed.…”
Section: Discussionsupporting
confidence: 81%
“…Since there are no IgG antibody-producing cells among ABC in low responder mice, it is clear that the ABC detected must be precursor or memory cells, which bear IgG on their surface. The formation of precursor cells of the IgG type after antigenic stimulation concurs with the findings of other investigators (30)(31)(32)(33). Furthermore, the results obtained show that in low responders the differentiation of IgG precursor or memory cells into IgG antibody-forming cells is not completed.…”
Section: Discussionsupporting
confidence: 81%
“…Anti-DNP antibody-secreting cells are bound by DNP-agarose conjugates equally well whether GPA or BSA is the protein carrier (6) and it has been shown that anti-Ig inhibits binding of antibody-secreting cells to antigen-glass bead columns (16). Thus, ABC and antibody-secreting cells appear to have similar surface receptors and these receptors resemble circulating antibody molecules in that they are immunoglobulins, they are hapten specific, and an avidity increase occurs in the course of the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…By hypothesis, the specific combination of antigen with its receptor(s) results in activation of immune differentiation and subsequent synthesis of antibody, although under certain conditions specific inactivation and tolerance can ensue (1,2). Antigen receptors located on the surface of certain lymphoid cells (3)(4)(5)(6)(7)(8)(9) are considered to be representative of the eventual cell product with regard to both specificity and immunoglobulin class (10)(11)(12)(13). Therefore, the use of antibody directed against a particular class of heavy chain determinants displayed by antigen receptors could conceivably lead to the selective inhibition of the production of that immunoglobulin class resulting in an experimental dysgammaglobulinemia.…”
Section: (From the Department Of Immunology Mayo Medical School Rocmentioning
confidence: 99%